APPROVED DESTINATION STATUS (ADS) TIONGKOK SEBAGAI ECONOMIC STATECRAFT PADA KANADA TAHUN 2009 - Windari, Made; Priadarsini, Ni Wayan Rainy; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT China realized the economic statecraft strategy through Approved Destination Status (ADS) in Canada. ADS is an outbound tourism policy that functions as a control scheme for China's relations with countries that have been approved as tourist destinations and control of its citizens who conduct outbound tourism. The use of ADS as a form of diplomacy is because China seeks to eliminate the image of China Threat so that China can further expand its foreign policy and economic interests. The international situation also influenced China's decision to use ADS as a form of diplomacy. But since the Harper government, Canada has given harsh criticisms to China on issues of human rights, finance, investment, etc. Besides that, Canada gave an honorary citizenship title to the Dalai Lama, known for his anti-china views. China then postponed the administration of ADS as a reaction to Canada's attitude. Furthermore, this research will describe the use of ADS as economic statecraft in Canada. This research shows that ADS can function as a stick with the delay as well as providing ADS as a reward after normalization of relations after Harper's visit to Beijing in 2009. Data in this research were collected from many sources such as website, reports, journals, books etc. To analyze, this research used determinants foreign policy and economic statecraft concept. Keywords: Approved Destination Status (ADS), Tourism Diplomacy, Economic Statecraft.